(NaLEKSANDRA nIKOLAEWI^ sKRQBIN(B.s (NmONOGRAFIQs - (Nw(B. (Nw(B, (NrUBCOWAs ((NmOSKWA(B. s (NmUZYKAs, 1989)
(Nw KNIGE WOSSOZDAETSQ TWOR^ESKIJ WELIKOGORUSSKOGO KOMPOZITORA RASKRYWAETSQ SWOEOBRAZIE EGO INDIWIDUALXNOSTI I MIROWOZZERENIQ(B.s
Keywords: (NMONOGRAFIQs